Beholde og rekruttere sykepleiere til sykehjem, en kvalitativ studie av avdelingssykepleieres erfaringer - Hege Berge; Grethe Eilertsen (Septentrio Academic Publishing, 2020)
Retaining and recruiting nurses in nursing homes, - a qualitative study of nurse managers' experiences The purpose of the study was to explore nurse managers in Norwegian nursing homes experiences with retaining and recruiting of nurses. The study has a qualitative exploratory design. Ten nurse managers in nursing homes were interviewed. Two main themes emerged from the analysis: "Retaining nurses - a difficult line to balance" and "Recruiting - a field of excellence with ideals and reality". Retaining and recruiting nurses challenged nurse managers in finding a balance between facilitating professional development, supporting the nurses in independent prioritization of tasks as well as economic and organizational work that were occasionally perceived as an obstacle. Nurse managers play an important role in the nursing homes and influence nurses' retaining rate through active leadership. Good leadership may lead to a good reputation, which in turn is vital in retaining and recruiting nurses.